1997
DOI: 10.1159/000127240
|View full text |Cite
|
Sign up to set email alerts
|

Endocrine Profile and Neuroendocrine Challenge Tests in Transgenic Mice Expressing Antisense RNA against the Glucocorticoid Receptor

Abstract: A transgene expressing antisense RNA complementary to a fragment of the glucocorticoid receptor cDNA was incorporated into the mouse genome and resulted in a transgenic animal that has decreased glucocorticoid receptor function. The transgenic mice showed basal plasma ACTH and corticosterone levels similar to those of the normal control animals. We have further investigated changes in HPA axis regulation by use of different neuroendocrine challenge tests including a dexamethasone suppression test (DST). In com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
62
1

Year Published

1999
1999
2011
2011

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(68 citation statements)
references
References 30 publications
5
62
1
Order By: Relevance
“…Although the DST is most likely working at the pituitary level (99), the underlying disregulation is undoubtedly of CNS origin and reflects increased drive upon the CRH and AVP systems of the hypothalamus (45) and constitutes a form of endogenously driven stress. A lessening of the adrenal steroid feedback effects on the hippocampus might be a contributing factor to elevated HPA activity in depression, and recent studies of Barden and co-workers with a transgenic mouse strain (7,56) have suggested that decreased forebrain Type II receptor expression might be a contributing factor to depression and a potential target of antidepressant therapy (56,102). It is not clear, however, how much hippocampal Type II receptor expression, as opposed to receptor expression in other brain regions, is a key factor.…”
Section: The Hippocampus and Hpa Regulationmentioning
confidence: 98%
“…Although the DST is most likely working at the pituitary level (99), the underlying disregulation is undoubtedly of CNS origin and reflects increased drive upon the CRH and AVP systems of the hypothalamus (45) and constitutes a form of endogenously driven stress. A lessening of the adrenal steroid feedback effects on the hippocampus might be a contributing factor to elevated HPA activity in depression, and recent studies of Barden and co-workers with a transgenic mouse strain (7,56) have suggested that decreased forebrain Type II receptor expression might be a contributing factor to depression and a potential target of antidepressant therapy (56,102). It is not clear, however, how much hippocampal Type II receptor expression, as opposed to receptor expression in other brain regions, is a key factor.…”
Section: The Hippocampus and Hpa Regulationmentioning
confidence: 98%
“…Mice with decreased glucocorticoid receptor gene expression (by transgenic expression of antisense mRNA directed against the receptor) exhibit reduced hypothalamic CRH expression [20], enhanced stress-associated ACTH response [21][22][23], and impaired efficiency of glucocorticoid-mediated negative feedback [21,[23][24][25]. These mice exhibit deficits in spatial learning, enhanced responses to novelty and decreased locomotion in familiar environments [6].…”
Section: Modulation By Mineralocorticoid and Glucocorticoid Receptorsmentioning
confidence: 99%
“…These transgenic mice displayed impaired endogenous GR function and were characterized by dysfunctional glucocorticoid inhibitory feedback and disturbed ACTH and corticosterone secretory responses Karanth et al 1997;Dijkstra et al 1998). Long-term treatment of the transgenic mice with antidepressant drugs caused an increase in GR gene expression and produced significant normalization of the HPA system hyperactivity through restoration of functional glucocorticoid inhibitory feedback (Pepin et al 1992b;Barden et al 1995;Barden et al 1997).…”
Section: Abstract : Creb; Antidepressant Drugs; Glucocorticoid Recepmentioning
confidence: 99%
“…These transgenic mice displayed impaired endogenous GR function and were characterized by dysfunctional glucocorticoid inhibitory feedback and disturbed ACTH and corticosterone secretory responses Karanth et al 1997;Dijkstra et al 1998). Long-term treatment of the transgenic mice with antidepressant drugs caused an increase in GR gene expression and produced significant normalization of the HPA system hyperactivity through restoration of functional glucocorticoid inhibitory feedback (Pepin et al 1992b;Barden et al 1995;Barden et al 1997).Because the second messenger cyclic AMP plays a central role in signaling within the HPA axis, long-term adaptations in cAMP regulated gene expression are critical to chronic HPA dysfunction (Hatalski and Baram 1997). Given that depressed patients display reduced cAMP protein kinase activity (Shelton et al 1996) and that the cAMP/PKA cascade is involved in mediating the action of antidepressant drugs, GR dysfunction and disruption of proper cAMP/PKA signaling both observed in depression are highly interdependent.…”
mentioning
confidence: 99%